Political and Media Polarization: Dynamics, Consequences, and Perspectives in Contemporary Society. - Battista, Daniele; Cillingová, Veronika; Gugliucciello, Arthur (Academicus, 2026)
This contribution examines the relationship between political and media polarization in contemporary society. Over the years, polarization has become a central phenomenon in multiple countries, characterized by the progressive separation of opinions and extreme attitudes among different political groups. The media, absolute protagonists in the dissemination of information and in the shaping of public opinion, stand as a stronghold of this process. This article first presents a conceptualization and examines its link with the media landscape, establishing its origin, consequences, and the different ramifications. The effects impact society’s media consumption and the very functioning of democracy, strongly affecting political life. Possible trajectories and strategies are therefore addressed to promote a more constructive and less polarized public discourse.